Quality of life and healthy aspects in agribusiness workers (Bioscience Journal, 2018)
to evaluate quality of life and its relationship to lifestyle along with the personal and work characteristics of agro-industry workers from Goias, Brazil. A cross-sectional, descriptive and quantitative study, using the WHOQOL-BREF instrument as well as personal and work data, the data collection occurred in 2014. A bivariate analysis was used to check for associations between the predictor variables and the analyzed outcomes. Variables with p < 0.20 and potential confounding variables: gender, age, income and marital status were included in multiple linear regression models. The perception of the quality of life of workers showed better scores for the social domain and worse for environment, obtaining significance for the factors associated with quality of life: physical activity, education, skin color, work related accidents, income and body mass index. In order to perform the multifactorial analyses, the associated independent factors were confirmed in the regression analysis, with the inclusion of the variables gender, marital status and alcohol consumption. The workers have lifestyles that interfere with the perception of their quality of life. All of the domains evaluated in this study were shown to possess this interference, with prevalence toward a lack of physical activity and the occurrence of work related accidents.